SELECTION OF DIGITAL TOOLS FOR ORGANIZING STUDENTS' GROUP WORK IN DISTANCE EDUCATION - Olena G. Glazunova; Andrii M. Hurzhii; Valentyna I. Korolchuk; Tetiana V. Voloshyna (Інформаційні технології і засоби навчання)
The transformation of classical education into distance education has become increasingly relevant, especially given the challenging conditions posed by the COVID-19 pandemic and military operations in our country. In these circumstances, distance learning requires practical educational materials that are easily accessible to students. This paper proposes criteria and indicators for selecting digital tools that can facilitate group work with educational content in distance learning. We analyzed the tools available on the Microsoft 365, Google Workspace, and Cisco Webex platforms and evaluated their suitability for managing students’ group work in distance learning in institutions of higher education at various stages of the learning process including setting tasks, designing the learning environment, facilitating group interaction and communication, managing educational content and files, promoting teamwork and productivity, and presenting results. To obtain expert assessment of the defined criteria and indicators, we engaged seventeen researchers and educators who have practical experience using digital tools in distance learning. Our study identified three important criteria for selecting digital tools for group work with educational content, namely: design, functional-technological, education-communication ones. We determined the weight of the indicators for these criteria and assessed digital tools for group work with educational content in distance learning. Digital tools such as Microsoft 365 and Google Workspace was found to be more suitable for providing group work of students in a distance learning, while Cisco Webex was found to be the most suitable tool for organizing real-time group work. Other digital tools for group work of students in distance learning can be evaluated according to defined criteria and indicators.